2017
DOI: 10.19082/4370
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation practice in Egyptian pediatric intensive care units

Abstract: IntroductionMechanical ventilation is one of the indispensable tools in pediatric intensive care units. Few studies addressed the epidemiology of pediatric patients on mechanical ventilation and the frequently used modes of ventilation. This is the first study to describe the practice of mechanical ventilation (MV) in Egyptian pediatric intensive care units (PICUs).MethodsThis prospective observational study was conducted from January 2014 to December 2014 in two pediatric intensive care units at Cairo Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
2
7
2
Order By: Relevance
“…In the present study, a prevalence of 21.6% of AE was observed (36 AE per thousand days of MV), which is lower than the studies by Kendirli et al 12 (42.8%), Meligy et al 13 (39.9% or 29.5 AE per thousand days of MV), De Jesus et al 3 (51.3%) and Principi et al (40% or 114 AE per thousand days of MV). 15 We also found that 16.6% of patients suffered two AE, similar to the study by Meligy et al, 13 in which 11.9% suffered more than one AE. The variation in prevalence found can be influenced by the selection made by each author regarding which events to analyze.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In the present study, a prevalence of 21.6% of AE was observed (36 AE per thousand days of MV), which is lower than the studies by Kendirli et al 12 (42.8%), Meligy et al 13 (39.9% or 29.5 AE per thousand days of MV), De Jesus et al 3 (51.3%) and Principi et al (40% or 114 AE per thousand days of MV). 15 We also found that 16.6% of patients suffered two AE, similar to the study by Meligy et al, 13 in which 11.9% suffered more than one AE. The variation in prevalence found can be influenced by the selection made by each author regarding which events to analyze.…”
Section: Discussioncontrasting
confidence: 78%
“…11 Studies in the pediatric age range are still restricted, with a limited number of cases describing VAP more commonly, reinforcing the purpose and relevance of this study to assess the prevalence, types of events, and factors associated with the occurrence of AE related to MV in children and adolescents. 3,[11][12][13][14][15][16][17] The results of the present study showed a significant number of AEs that can be prevented, identifying the length of hospital stay as a risk factor to be monitored and evaluated regarding the prevention of these occurrences.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The present study found lower VAP rates compared to a recent six-month prospective study in 16 PICUs in the USA, which found 7.1 per 1000 ventilator days (Gupta et al, 2014). These differences may be due to the demographic variations in respective PICUs, institutional preventative strategies, and varying treatment options (Awasthi et al, 2013;Bassant Salah, Sally, & Seham Awad El, 2017;Srinivasan et al, 2009).…”
Section: Discussion Of Demographic and Outcome Variables Of The Prospcontrasting
confidence: 66%
“…It is well-documented that IMV is an independent risk factor in the prognosis of children in PICU [ 11 , 12 , 13 ]. In this study, GGT was significantly higher in patients with IMV use, and the ROC curves showed that the GGT score covered an AUC of 0.609 for a cutoff value of 30.6 IU.…”
Section: Discussionmentioning
confidence: 99%